2007
DOI: 10.1128/jvi.02500-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Immunodeficiency Virus Type 1 Monomeric and Trimeric gp120 Glycoproteins Stabilized in the CD4-Bound State: Antigenicity, Biophysics, and Immunogenicity

Abstract: The human immunodeficiency virus type 1 exterior gp120 envelope glycoprotein is highly flexible, and this flexibility may contribute to the inability of monomeric gp120 immunogens to elicit broadly neutralizing antibodies. We previously showed that an S375W modification of a critical interfacial cavity central to the primary receptor binding site, the Phe43 cavity, stabilizes gp120 into the CD4-bound state. However, the immunological effects of this cavity-altering replacement were never tested. Subsequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
150
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(167 citation statements)
references
References 47 publications
17
150
0
Order By: Relevance
“…The majority of immunogens studied to date elicit sera that neutralize a subset of Tier 1 viruses but fail to neutralize most Tier 2 and 3 viruses. Consistent with earlier studies (18,19), sera from the control group largely neutralized Tier-1 neutralization-sensitive viruses. Depletion studies and competition binding assays with b12 showed that the antibodies in the broadly neutralizing sera are gp120-directed, and an appreciable fraction of antibodies in group 3 sera is directed toward the CD4 binding site.…”
supporting
confidence: 78%
“…The majority of immunogens studied to date elicit sera that neutralize a subset of Tier 1 viruses but fail to neutralize most Tier 2 and 3 viruses. Consistent with earlier studies (18,19), sera from the control group largely neutralized Tier-1 neutralization-sensitive viruses. Depletion studies and competition binding assays with b12 showed that the antibodies in the broadly neutralizing sera are gp120-directed, and an appreciable fraction of antibodies in group 3 sera is directed toward the CD4 binding site.…”
supporting
confidence: 78%
“…Serum from macaque 841, which neutralized the virus in the absence of sCD4, showed only a modest increase in potency in the presence of sCD4. Of note, this variable pattern of neutralization among the rhFLSCimmunized macaques resembles what was measured in a similar assay of rabbit sera raised against stabilized envelope trimers that present CD4-induced epitopes (30). In comparison, serum from only one animal in the gp120-CD4 XL group (macaque 842) exhibited neutralizing activity in the presence of sCD4 (Fig.…”
mentioning
confidence: 82%
“…The resistance of most primary HIV-1 Envs to sCD4 engagement may explain why sCD4 exhibited only minimal in vivo potential as an antiviral agent (44). CD4mc have been shown to sensitize HIV-1 virions to neutralization by otherwise nonneutralizing CD4i Abs that can easily be generated through vaccination with CD4-bound stabilized gp120s (25,45,46). Importantly, these types of Abs were isolated from RV144 vaccinees and possessed ADCC potential (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the dual effect of these CD4mc (i.e., sensitization of HIV-1 viral particles to neutralization and infected cells to ADCC by CD4i Abs) might help limit viral transmission. Such CD4i Abs are elicited early and in a high proportion of infected individuals (11,17) and can also be elicited by vaccination with "stabilized gp120 cores" that have been engineered to assume the CD4-bound state (45). One can envision a multicomponent vaccine regimen in which one of the immunogens is a stabilized gp120 core that elicits CD4i Abs and CD4mc administered orally or in a microbicide formulation that could sensitize a range of T/F viruses and infected cells to inhibition by the vaccine-elicited Abs.…”
Section: Discussionmentioning
confidence: 99%